Remember the Mothers: The Safe Motherhood Quilt Project. Issue 3 (May 2018) - Callister, Lynn Clark
Abstract : The Safe Motherhood Quilt Project, was generated to honor women in the United States who lost their lives during the childbirth process over the past thirty-five years. Our global health and nursing expert, Dr. Callister, explains the nature and importance of this project.